DIFFERENT EXPRESSION SIGNATURES OF GENES RELATED TO PRRSV INFECTION AND RESISTANCE IN HEALTHY LUNG TISSUES FROM FOUR CHINESE PIG BREEDS - Yuxin Song; Jiuzhou Xue; Ying Yang; Zheng Feng; Yangli Pei; Jiju Li (Journal of Animal and Plant Sciences, 2023)
Porcine reproductive and respiratory syndrome (PRRS) is a chronic disease, which is related to reproductive and respiratory and caused by PRRS virus (PRRSV) binding to specific porcine receptors in pigs. Different pig breeds have different infection and resistance abilities to PRRSV. To study the expression levels of genes related to PRRSV infection and resistance in healthy lung tissues form different pig breeds, we collected lung tissue from healthy Tibetan pigs (TB), Wuzhishan pigs (WZS)，and Meishan pigs (MS), as well as Bama mini-pigs (BM). For each breed, we used three independent biological replicates. Real-time fluorescence quantitative PCR (RT-qPCR) was performed to detect the expression levels of CD163, CD169, CD151, MYD88, TRAF6, TLR3, IFN-α, IFN-γ, IL-1β, IL-6, IL-8, CCl4, NF-kB, and CD86. The results showed that CD163, CD169, CD151, IFN-α, IFN-γ, IL-1β, CCl4 and NF-kB had significant differences among different breeds. Our results of different related gene expression among pig breeds might provide new insights into the genetic strategies for improvement of resistance to PRRSV infection in pigs.
Keywords: PRRSV receptor genes; IFN-α; IFN-γ; IL-1β; CCl4; NF-kB